The other digital China nonconfrontational activism on the social web - Wang, Jing, 1950- (Harvard University Press, 2019)
The Other Digital China: Nonconfrontational Activism on the Social Web maps out the emerging ecosystem of Chinese activism 2.0 that traverses multiple sectors-the NGO sector, universities, the corporate sector, and the IT sector-where change agents are creating social good in non-contentious ways and engaged in constructing the new "social" under difficult ideological constraints. Focusing on social media and tech practices emerging from China's social sector in recent years, this book provides a multifaceted look at the Chinese society caught at a transformative moment, thanks in part to the arrival of Web 2.0 technology and the accompanying cyber utopianism, as well as the Communist Party's recently alleged commitment to policies aimed at energizing the hitherto weak social structure. Wang develops the idea of "nonconfrontational activism" and argues that it's possible to talk about the agency of "change-makers" even in authoritarian countries.--